Challenges in the implementation of employment equity act : a case study of the University of Limpopo - Phaduli, Takalani Violet (My University, 2020)
The purpose of this study was to investigate challenges in the implementation of Employment Equity Act in the University of Limpopo. The design of the research in this study is both qualitative and quantitative. Data were collected from HODs and Human Resources Officers. Structured interviews and questionnaires were used to collect data form the participants. Data were analysed quantitatively and qualitatively. Results revealed that there are more males in Senior Management levels than females in the University. Data further showed that the majority of Senior Management fall under age category 50-64 years old. The results show that most of the respondents hold highest qualifications which is masters and doctoral degree. It was found that most of the respondents are from Sepedi and Tshivenda speaking communities. The finding revealed that the University of Limpopo has been implementing the Employment Equity Act. However, the implementation of the EEA encountered certain challenges including among other resistant to change, poor networking, lack of employment equity awareness, undermining of the HR Officers by Selection Committee members and lack of qualified people with disabilities in certain positions. Another finding shows that the University has Employment Equity Plan with numerical target to be achieved. It found that the successful implementation of EEA will address the problem of unfair discrimination that people suffered as a result of race, gender, disability and sexual orientation. The findings further show that the University is strictly adhering to the stipulations of the EEA. It was found that employees in the University are not well informed of the Employment Equity Policies. Another finding shows that the University Employment Equity has been a very useful tool to promote equality in the University. The study recommends that the University should not deviate from the EEA especially when filling positions reserved for designated groups. It is recommended that HODs should familiarize themselves with the Act. It is recommended that the University use provincial demographics to set the EE targets. University must have EE Plan targets on the agenda at all meetings of the University’s Executive Committees. It is recommended that further discussion and monitoring need to be conducted at Executive Management level.
Thesis (MPA.) -- University of Limpopo, 2020
Keywords: Employment equity act; Employment equity plan; HODs; EE targets; Employment equity policies; Discrimination in employment -- South Africa -- Limpopo; Affirmative action programs -- South Africa -- Limpopo